Complex dynamic analysis of risk-averse newsvendor models with buyback guarantee financing. Issue 9 (3rd May 2022) - Chen, Jianxin; Zhang, Tonghua; Zhou, Yong-wu; Hou, Rui
Abstract : In the framework of the newsvendor model, both single- and multi-period models are proposed to investigate the ordering strategy of a risk-averse retailer under buyback guarantee financing (BGF) and stochastic demand. In the single-period model, the classical newsvendor is extended by introducing risk aversion and capital constraints simultaneously. It is found that the optimal ordering quantity is a monotonic function in some parameters, such as increasing in the retailer's risk aversion and salvage value, while decreasing in the initial capital and wholesale price. The multi-period model is a dynamical model described by the bounded rationality decision adjustment rules. We then investigate the complex dynamics they admit, such as period-doubling bifurcation and chaotic phenomena, and have found that the dynamical models experience more complex behaviour than their static counterpart. Furthermore, in the dynamical case, we could see periodic, bifurcating or chaotic changes in ordering quantity. We also investigate the influence of BGF on ordering quantity, which may lead to a risk-averse retailer to order aggressively. Finally, some numerical simulations are given to illustrate the theoretical results and some suggestions are also provided.